Instrumen Penilaian pada Materi Hidrolisis Garam: Studi Literatur - Mahdiyah, Hanifa; Guspatni (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Salt hydrolysis is a fundamental concept in high school chemistry education, but it often leads to student misconceptions. This study aims to analyze these misconceptions and evaluate the instruments used to assess students' understanding. A literature review was conducted to examine research on instruments for analyzing misconceptions, learning outcomes, and skills related to salt hydrolysis. The analysis revealed common misconceptions in understanding salt hydrolysis and the properties of salts, as well as challenges in measuring pH values of solutions resulting from reactions between weak acids and strong bases. Misconceptions were found at both symbolic and submicroscopic levels of chemical representation. Effective evaluation instruments for measuring misconceptions in salt hydrolysis include two-tier, three-tier, four-tier, and five-tier diagnostic tests, as well as tests based on High Order Thinking Skills. These instruments help identify misconceptions, measure learning outcomes, and evaluate student skills.